Digital Marketing Strategy for Mangrove Ecotourism Towards Sustainable Development Goals (SDG) 8.3 (Case Study: Rawa Aopa Watumohai National Park, Southeast Sulawesi) - Salam, Salmiya Ismail; Lubis, Ratna Lindawati (MSJ : Majority Science Journal, 2024)
The purpose of this research is to analyze the external and internal environment, including opportunities, challenges, strengths, and weaknesses, regarding the Digital Marketing Strategy for Mangrove Ecotourism towards SDG 8.3 at Rawa Aopa Watumohai National Park. This research method utilizes a qualitative approach with SWOT analysis. Findings reveal that the Park supports various training and capacity-building activities for local entrepreneurs around the Park, reflecting the local community's enthusiasm for entrepreneurship, thus establishing a connection between SDG 8.3 and the Park. Weaknesses include the need for improvement in the quantity of tourism facilities, transportation, public infrastructure, and internet connectivity. Opportunities arise from leveraging social media for optimal promotion of tourism locations to attract tourists. Threats stem from competition with similar tourist destinations, potentially reducing visitor numbers. Additionally, climate change and threats to species diversity in the park necessitate better management planning.